Of health journalism to digital environment. An analysis of journalistic practices in Mexican cybermedia - Rivera Terrazas, José Israel (2019)
Currently, it is common to find not only sections of health journalism adapted to their digital media but also specialized media created to generate exclusive content for the Internet, as well as journalists, who are the key players in the process of construction and contextualization of health information, and are better adapted to the Internet to meet the expectations and demands of users who increasingly depend on new technologies. Using in-depth interviews conducted with ten journalists from four Mexican cybermedia, this article analyzes how health journalism adapts to the interactivity, hypertextuality, multimedia and immediacy of cyberjournalism to carry out journalistic practices that allow the construction of informative content. Moreover, it reveals that the shortage of journalists in cybermedia and the lack of skills related to the digital environment represent the main obstacles for the adaptation of health journalism.